Some Economic Consequences of India's Institutions of Governance: A Conceptual Framework - Nirvikar Singh (University of California, Economics Department, 2003)
This paper examines the functioning of some of India's institutions of governance, namely, the legislative and executive branches of government, the judiciary, and the bureaucracy, from an instrumental, economic perspective. Governance is analyzed along three dimensions: (1) the degree of commitment or durability of laws and rules, (2) the degree of enforcement of these laws, and (3) the degree of decentralization of jurisdictions with respect to local public goods. It is suggested that India's experience of governance reflects insufficiencies in all three dimensions: of durability, enforcement, and decentralization, with adverse consequences for economic efficiency. The paper concludes with a brief normative discussion of collective action in general, and alternative structures of institutions of governance.
Keywords: 330; governance; commitment; durability; enforcement; decentralization